KP372-1-Induced AKT Hyperactivation Blocks DNA Repair to Synergize With PARP Inhibitor Rucaparib via Inhibiting FOXO3a/GADD45α Pathway - Jiang, Lingxiang; Liu, Yingchun; Su, Xiaolin; Wang, Jiangwei; Zhao, Ye; Tumbath, Soumya; Kilgore, Jessica A.; Williams, Noelle S.; Chen, Yaomin; Wang, Xiaolei; Mendonca, Marc S.; Lu, Tao; et al. (Frontiers in Oncology, 2022)
Poly (ADP-ribose) polymerase (PARP) inhibitors (PARPi) have exhibited great promise in the treatment of tumors with homologous recombination (HR) deficiency, however, PARPi resistance, which ultimately recovers DNA repair and cell progress, has become an enormous clinical challenge. Recently, KP372-1 was identified as a novel potential anticancer agent that targeted the redox enzyme, NAD(P)H:quinone oxidoreductase 1 (NQO1), to induce extensive reactive oxygen species (ROS) generation that amplified DNA damage, leading to cancer cell death. To overcome PARPi resistance and expand its therapeutic utility, we investigated whether a combination therapy of a sublethal dose of KP372-1 with a nontoxic dose of PARPi rucaparib would synergize and enhance lethality in NQO1 over-expressing cancers. We reported that the combination treatment of KP372-1 and rucaparib induced a transient and dramatic AKT hyperactivation that inhibited DNA repair by regulating FOXO3a/GADD45α pathway, which enhanced PARPi lethality and overcame PARPi resistance. We further found that PARP inhibition blocked KP372-1-induced PARP1 hyperactivation to reverse NAD+/ATP loss that promoted Ca2+-dependent autophagy and apoptosis. Moreover, pretreatment of cells with BAPTA-AM, a cytosolic Ca2+ chelator, dramatically rescued KP372-1- or combination treatment-induced lethality and significantly suppressed PAR formation and γH2AX activation. Finally, we demonstrated that this combination therapy enhanced accumulation of both agents in mouse tumor tissues and synergistically suppressed tumor growth in orthotopic pancreatic and non-small-cell lung cancer xenograft models. Together, our study provides novel preclinical evidence for new combination therapy in NQO1+ solid tumors that may broaden the clinical utility of PARPi.